Evaluación de la dimetilacetamida como crioprotector de espermatozoides epididimarios bovinos seleccionados con percoll - Fernández Campoverde, Jorge Oswaldo (2024)
The development of reproductive biotechnologies allows the conservation of the genetic material of various species either of commercial interest, in danger of extinction, or that cannot continue with their physiological reproductive process. The use of suitable cryoprotectors allows for successful seminal cryopreservation. This research paper is aimed to evaluate dimethylacetamide as a cryoprotector of bovine epididymal spermatozoa selected with percoll. We used 20 pairs of bull epididymides and the sperm were obtained using the retrograde flow collection method, totalling 7 pulls of sperm samples. Each pull was distributed in 4 cryopreservation treatments: Glycerol 6%, Glycerol 6% + centrifugation, Dimethylacetamide 6% and Dimethylacetamide 6% + centrifugation. In the centrifugation process, spermatozoa were obtained using a 90% Percoll density gradient. Progressive individual motility (%), sperm viability (%), sperm morphological abnormalities (%) and sperm membrane integrity (HOECHST/PI%) were evaluated. A diluent effect was observed (p < 0001), but there was no centrifugation action (p≥ 0.05). When using the 6% glycerol diluent, progressive individual motility (60.59 ± 2.94) %, sperm vitality (59.47 ± 2.97) % and the number of sperm cells with an intact HOECHST membrane (52.57 ± 1.59) were higher compared to Dimethylacetamide 6% (39.88 ± 2.94; 23.71 ± 2.97; 34.73 ± 1.59) respectively. Also, there was an interaction (p = 0.02) between the type of diluent and centrifugation on sperm vitality, where the centrifuged 6% Dimethylacetamide samples had a higher percentage of living cells than without centrifugation. It was concluded that the use of 6% Dimethylacetamide as a cryoprotector is less efficient than 6% Glycerol, but centrifugation prior to seminal cryopreservation with 6% Dimethylacetamide promotes sperm quality.